Does Farmers’ Participation in Skills Training Improve Their Livelihood Capital? An Empirical Study from China - Huaquan Zhang; Mingxi Yang (Agriculture)
With the rapid development of China’s rural economy, rural collective economic organizations have played a significant role in increasing farmers’ income and promoting rural revitalization. This study aims to explore the impact of farmers’ participation in skills training organized by rural collective economic organizations on their livelihood capital and the underlying mechanisms. Using tracking survey data from rural households in Chongzhou City, Sichuan Province, in 2023, the paper employs empirical analysis methods, including OLS and mediation effect analysis. The results show that participation in skills training organized by rural collective economic organizations enhances farmers’ livelihood capital. The effectiveness of public service delivery by village committees, the network role of farmers’ cooperatives, and the linkage effect of leading agricultural enterprises in driving rural development act as mediating factors. Additionally, the impact of skills training on farmers’ livelihood capital varies according to household characteristics and the attributes of the rural collective economic organizations involved. Therefore, this paper proposes the following policy recommendations: (1) Further strengthen the public service and resource allocation functions of the village committees. (2) Support and optimize the operating entities such as farmer cooperatives and leading agricultural industrialization enterprises. (3) Address the training needs of different groups and enhance the focus and support of grassroots governments for skills training in collective economic organizations.